THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND E-COMMERCE BUSINESS COMMUNICATIONS PERSPECTIVE ON ENTREPRENEUR SELF EFFICACY MEDIATED INTENSITY IN STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS UNIVERSITAS NEGERI SURABAYA - Rosi Andriani; Agus Hermawan; Nurika Restuningdiah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The importance of this study aims to examine the effect of entrepreneurship education and the perspective of e-commerce business communication on entrepreneurial intensity mediated by entrepreneur self-efficacy in students of the economics and business faculties of Surabaya State University. This research uses a type of descriptive quantitative research with path analysis to look for relationships in each variable. The number of samples was 303 students from a total population of 1253 students from the 2019-2021 class. The research findings reveal that entrepreneurial intentions are indirectly influenced by entrepreneurship education, which means that entrepreneur self-efficacy has succeeded in mediating entrepreneurship education on the entrepreneurial intensity of students at the Faculty of Economics and Business, Universitas Negeri Surabaya. As for the e-commerce business perspective, it does not significantly influence the entrepreneurial intensity of students at the Faculty of Economics and Business Universitas Negeri Surabaya